2015
DOI: 10.3390/w7063024
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Willingness to Pay to Improve Water Supply Services: Application of Contingent Valuation Method

Abstract: Safe water supply is one of the important Millennium Goals. For development of market water supply services, the willingness of consumers to pay is essential. The consumers' willingness to pay (WTP) for piped water supply using the contingent valuation (CV) method with different starting point bids was investigated for the Pavlodar Region, Kazakhstan. The results showed that households with access to groundwater (well or borehole water users) perceived this as of good quality. Consumers without access to groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 14 publications
1
41
1
2
Order By: Relevance
“…In the pilot study, 10 villages were randomly selected for a study on willingness to pay for water supply. The results of the pilot study were reported by Tussupova et al [7]. The rest of the villages, in total 27 rural villages of different size, were investigated in the present survey conducted during July–August 2013.…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…In the pilot study, 10 villages were randomly selected for a study on willingness to pay for water supply. The results of the pilot study were reported by Tussupova et al [7]. The rest of the villages, in total 27 rural villages of different size, were investigated in the present survey conducted during July–August 2013.…”
Section: Methodsmentioning
confidence: 77%
“…One missing but interesting question to borehole water users is if water is connected from the borehole to the home. From the pilot study, it was seen that those who have connected water to the home and have a water boiler at home regardless of income have low or no willingness to connect to the piped tap water [7]. One of the reasons is that usually in rural areas cold water only is given through the pipes and households have to heat it by themselves using water boilers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present the main challenge for Central Asian states public health sectors is in clarifying, coordinating, and streamlining Consequently, all five Central Asian states have experienced the crumbling of the Soviet Union in 1991, the following collapse of the economic system, and the subsequent socioeconomic upheaval [2]. The transition from state planned to market economy has meant changing patterns for basic services such as water supply and sanitation [3]. At present Central Asia is home to a population of about 66 million (Kazakhstan 17.0 million, Kyrgyzstan 5.7 million, Tajikistan 8.0 million, Turkmenistan 5.2 million, and Uzbekistan 30.0 million) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Use of untreated wastewater to meet water shortage; 2 Lack of infrastructure, especially related to wastewater treatment and discharge; 3 Lack of health awareness and proper handling of polluted water; and 4…”
mentioning
confidence: 99%